2x+6+6x=86

Simple and best practice solution for 2x+6+6x=86 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+6+6x=86 equation:


Simplifying
2x + 6 + 6x = 86

Reorder the terms:
6 + 2x + 6x = 86

Combine like terms: 2x + 6x = 8x
6 + 8x = 86

Solving
6 + 8x = 86

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 8x = 86 + -6

Combine like terms: 6 + -6 = 0
0 + 8x = 86 + -6
8x = 86 + -6

Combine like terms: 86 + -6 = 80
8x = 80

Divide each side by '8'.
x = 10

Simplifying
x = 10

See similar equations:

| t^2-2t=20 | | 27x^2-18x+3=0 | | 10x^2+72x-64=0 | | 102-(4x+15)=4(x+6)+x | | y^2(y-4)=5y-14 | | 48-16= | | x^2+6x+13=x+5 | | 18-2g=4 | | S=-16t^2+48t | | 5x+93y=5 | | 5y+2=2(y-4) | | p(x)=x^3-x^2-4x-6 | | -(x-1)=4x-14 | | (3x^2+5x+2)+(8x^2-6)= | | 81-2x=25x+15 | | -5x+21=-7x+26 | | 2x+9=45-7x | | 9(4x+3)-2(2x-2)=-4 | | 2x^2-75=175 | | -3(m+2)+m=-22 | | 23b+(-19b)-1=31 | | (x^3+y^3)+13(-12xy)= | | (x^3+y^3)+13-(12xy)= | | (x^3+y^3)+13-12xy= | | 5(a-11)=-35 | | (x^3+y^3)-12xy+13= | | x^3+y^3-12xy+13= | | 8=5-c | | x^3-4x^2= | | 13+4y=5 | | 5x^2+30x-15=0 | | 5-2y+50=9y |

Equations solver categories